The Correlation Between Vocabulary Learning Strategies and the Vocabulary Mastery of the 2nd Grade Students of Junior High School Nurut Tauhid Labanasem-Kabat-Banyuwangi - Muhammad Teo Rizky Maulana; Ratu Ayu Sanggarina; Muhamad Darma Zikran; Arin Inayah; Achmad Nur Sidik (Jurnal Bina Ilmu Cendekia, 2025)
The objective of this research is to Investigate whether there is any the correlation between Vocabulary Learning Strategies and Vocabulary Mastery of eighth-grade students in junior high school Nurut Tauhid Labanasem-Kabat-Banyuwangi. In this research, the researcher used five vocabulary strategies including Metacognitive strategies, Cognitive strategies, Memory strategies, social strategies, and Affective strategies. For vocabulary mastery, it is grouped into four categories, namely Noun, Adjective, Verb, and Adverb. The results of the study showed that the coefficient r value of the calculation was 0.697 and the r of the table with N=15-2 sig 0.05 was 0.514 which showed that the coefficient r value was greater than the r of the table (0.697>0.514). Thus, it can be concluded that there is a correlation between vocabulary learning strategies and vocabulary mastery in 2nd-grade students of the junior high school of Labanasem Kabat Banyuwangi.